Answer:
E
Step-by-step explanation:
The expression given is: sec β - cos β ( i will write "beta" instead of the symbol β)
We know that [tex]sec(x)=\frac{1}{cos(x)}[/tex]
Substituting this into the the expression and doing some algebra manipulation, we have:
[tex]sec(beta)-cos(beta)\\=\frac{1}{cos(beta)}-cos(beta)\\=\frac{1-cos^{2}(beta)}{cos(beta)}[/tex]
Using the identity [tex]cos^{2}(x)+sin^{2}(x)=1\\[/tex] (also [tex]sin^{2}(x)=1-cos^{2}(x)[/tex]), we can now write:
[tex]\frac{1-cos^{2}(beta)}{cos(beta)}\\=\frac{sin^2(beta)}{cos(beta)}\\=\frac{sin(beta)*sin(beta)}{cos(beta)}\\=\frac{sin(beta)}{cos(beta)}*sin(beta)[/tex]
We know [tex]tan(x)=\frac{sin(x)}{cos(x)}[/tex], substituting this, we have:
[tex]\frac{sin(beta)}{cos(beta)}*sin(beta)\\=tan(beta)*sin(beta)[/tex]
Answer choice E is the right answer.